Biomineralization of mantis shrimp dactyl club following molting: apatite formation and brominated organic components - Chua, Isaiah Jia Qing (2024)
The stomatopod Odontodactylus scyllarus uses weaponized club-like appendages to attack its prey. These clubs are made of apatite, chitin, amorphous calcium carbonate, and amorphous calcium phosphate organized in a highly hierarchical structure with multiple regions and layers. We follow the development of the biomineralized club as a function of time using clubs harvested at specific times since molting. The clubs are investigated using a broad suite of techniques to unravel the biomineralization history of the clubs. Nano focus synchrotron x-ray diffraction and x-ray fluorescence experiments reveal that the club structure is more organized with more sub-regions than previously thought. The recently discovered impact surface has crystallites in a different size and orientation than those in the impact region. The crystal unit cell parameters vary to a large degree across individual samples, which indicates a spatial variation in the degree of chemical substitution. Energy dispersive spectroscopy and Raman spectroscopy show that this variation cannot be explained by carbonation and fluoridation of the lattice alone. X-ray fluorescence and mass spectroscopy show that the impact surface is coated with a thin membrane rich in bromine that forms at very initial stages of club formation. Proteomic studies show that a fraction of the club mineralization protein-1 has brominated tyrosine suggesting that bromination of club proteins at the club surface is an integral component of the club design. Taken together, the data unravel the spatio-temporal changes in biomineral structure during club formation. STATEMENT OF SIGNIFICANCE: Mantis shrimp hunt using club-like appendages that contain apatite, chitin, amorphous calcium carbonate, and amorphous calcium phosphate ordered in a highly hierarchical structure. To understand the formation process of the club we analyze clubs harvested at specific times since molting thereby constructing a club formation map. By combining several methods ranging from position resolved synchrotron X-ray diffraction to proteomics, we reveal that clubs form from an organic membrane with brominated protein and that crystalline apatite phases are present from the very onset of club formation and grow in relative importance over time. This reveals a complex biomineralization process leading to these fascinating biomineralized tools.